Knowledge, Attitude and Practice of Care Givers with Children Under Five Years of Age about Vaccination in Sunsari District, Nepal - Guragain, Parth; Rimal, Hem Sagar; Kafle, Tara Kumari (Birat Journal of Health Sciences, 2019)
Introduction: Immunization has shown major preventive aspects of infectious diseases, disability and death. Care giver is a person who provides direct care for children, elder people and chronically ill.Objectives: To assess the Knowledge, Attitude and Practice (KAP) of caregivers in Sunsari district about vaccination of under five children brought for vaccination at different private and government vaccination centers.Methodology: It is a cross sectional study that was carried out among 100 care givers from different places of Sunsari district for 3 months. The care givers completed a semi structured questionnaire that contains 4 different parts about the demographics, knowledge, attitude and practice of care givers toward immunization.Results: Most of the care givers have high level of awareness and importance of vaccination, which shows positive attitude and practice. The overall KAP was good among most of the caregivers (87.2%). The higher KAP level was positive associated with female gender, higher educational degree and having higher number of children.Conclusion: Most of caregivers from three different places of Sunsari districts had good KAP (in sense that most of the caregivers have awareness for quality and basic health standard) towards immunization which was associated with female gender and higher educational degrees. However, educational programs like community awareness and mobilizing Female Community Health Volunteers for providing appropriate knowledge of vaccination which increases the caregivers' knowledge, which might have change cognitive behavior. This study reflects the overall knowledge of caregivers towards immunization process which is very essential in childhood for prospective healthy future of the child.